2011
DOI: 10.1093/ejechocard/jer256
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical myocardial dysfunction in Rett syndrome

Abstract: These data indicate a previously unrecognized subclinical systo-diastolic biventricular myocardial dysfunction in typical and atypical RTT patients. A reduced preload is evidenced. The biventricular dysfunction is partially related to OS damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Mitochondrial dysfunction and its derived oxidative stress may contribute to RTT pathogenesis. Indeed, some RTT clinical signs such as hypotonia [49] and myocardial dysfunctions [50] correlate with mitochondrial dysfunctions and oxidative stress. In muscle and frontal lobe biopsies of RTT patients [48,51,52] and in cortex and hippocampus of MeCP2−/y mice [53], morphological alterations of mitochondria have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction and its derived oxidative stress may contribute to RTT pathogenesis. Indeed, some RTT clinical signs such as hypotonia [49] and myocardial dysfunctions [50] correlate with mitochondrial dysfunctions and oxidative stress. In muscle and frontal lobe biopsies of RTT patients [48,51,52] and in cortex and hippocampus of MeCP2−/y mice [53], morphological alterations of mitochondria have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Onset of symptoms and regression typically occur at 6 to 18 months of age after a period of apparently normal development [109]. Individuals with MECP2 -related disorder demonstrate autistic symptoms [110,111] as well as distinct features that include respiratory rhythm abnormalities, gait impairment, and cardiac complications [112,113]. …”
Section: Single Gene Disordersmentioning
confidence: 99%
“…Several previous studies reported cardiac abnormalities in both RTT patients and animal models1718. In our laboratory, Mecp2 -null mice exhibited reduced spontaneous movement between 3 and 8 weeks of age.…”
Section: Resultsmentioning
confidence: 64%
“…In RTT patients, recurrent apnea and breath-holding leads to significant hypoxic and oxidative stress, both of which are detrimental to many neuronal and cardiovascular functions4447. In fact, recent studies demonstrated that the levels of oxidative stress markers are increased, and correlated to LV systolic dysfunction, in RTT patients18. Those findings suggested that increased oxidative stress via respiratory depression may lead to aberrant ion channel and Cx43 expression, and predisposes the animal to arrhythmia and sudden death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation